2018
DOI: 10.3892/ol.2018.8011
|View full text |Cite
|
Sign up to set email alerts
|

High expression of estrogen-related receptor α is significantly associated with poor prognosis in patients with colorectal cancer

Abstract: Abstract. Colorectal cancer (CRC) is one of the most common types of malignancy with high morbidity and mortality rates worldwide. This biologically heterogeneous disease results in diverse therapeutic responses, thus, novel prognostic biomarkers are required to improve CRC treatment. Estrogen-related receptor α (ERRα) is a nuclear orphan receptor, which is associated with estrogen receptor α. The present study aimed to investigate the expression of ERRα in patients with CRC, and explore the association betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 31 publications
(40 reference statements)
5
24
1
Order By: Relevance
“…Colorectal cancer (CRC) is one of the most common malignancy types and the fourth most common cause of tumor associated mortality globally in 2008 (1). Despite improvements in the diagnosis and treatment of CRC, the efficacy of surgery and chemotherapy remains unsatisfactory, and the 5 year survival rate of patients with CRC with metastasis remains <10% in 2012 globally (2-4).…”
Section: Introductionmentioning
confidence: 99%
“…Colorectal cancer (CRC) is one of the most common malignancy types and the fourth most common cause of tumor associated mortality globally in 2008 (1). Despite improvements in the diagnosis and treatment of CRC, the efficacy of surgery and chemotherapy remains unsatisfactory, and the 5 year survival rate of patients with CRC with metastasis remains <10% in 2012 globally (2-4).…”
Section: Introductionmentioning
confidence: 99%
“…Testicular cancer was significantly increased in both construction and plastic industry workers [ 19 ]. All these cancer types are associated with disturbances of estrogen/testosterone ratio or of their receptors [ 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that ERRα-induced metabolic reprogramming can promote the survival of lapatinib-resistant cancer cells and demonstrates the potential of ERRα inhibition as adjunctive therapy for poor prognosis of HER2-positive breast cancer 26. High expression of ERRα was also found associating with poor prognosis in breast cancer,28 prostate cancer,29 colon cancer,30 ovarian cancer,31,32 endometrial cancer, and cervical cancer,33 while its association with LUAD has not yet been profiled. In this study, the positive expression of ERRα in lung cancer tissues was significantly higher than in paracancerous tissues.…”
Section: Discussionmentioning
confidence: 99%